1965
DOI: 10.1139/v65-346
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Vapor on the Formation of Modifications

Abstract: The two recognized forrns of calcium sulfate heniihydrate can be identified by the position of a relatively small exothermic peak in their differential thermograms. Hemihydrates prepared a t various water vapor pressures up to 760 mln Hg were found to produce this esotherniic peak in a position which is characteristic for the 0-for~il. These results indicate that a-hemihydrate cannot be made a t atmospheric pressure, as was previously suggested on the basis of heat solution measurements. The typical differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 4 publications
3
16
0
Order By: Relevance
“…Gypsum, or CaSO 4 ·2H 2 O, contains about 20.9% by mass chemically combined water, which is readily lost at an elevated temperature. This phenomenon is called dehydration, and the dehydration mechanism of gypsum has been intensively investigated so far . Groves reported that first CaSO 4 ·0.5H 2 O and then CaSO 4 is formed during gypsum dehydration, which was also confirmed by Kuntze and Paulik et al .…”
Section: Introductionmentioning
confidence: 80%
“…Gypsum, or CaSO 4 ·2H 2 O, contains about 20.9% by mass chemically combined water, which is readily lost at an elevated temperature. This phenomenon is called dehydration, and the dehydration mechanism of gypsum has been intensively investigated so far . Groves reported that first CaSO 4 ·0.5H 2 O and then CaSO 4 is formed during gypsum dehydration, which was also confirmed by Kuntze and Paulik et al .…”
Section: Introductionmentioning
confidence: 80%
“…They found that the two modifications were different in thermodynamic properties such as specific heat and heats of hydration. The difference noted by Powell in his DTA study (1958) is also a thermodynamic property, and this method has gained increased support for the identification of wet-and dry-calcined hemihydrate (Fleck et al, 1960;Kuntze, 1965;Miyazaki, 1966;Ball and Urie, 1970). The present study indicates that while the DTA method is valid for the identification of wet-and drycalcined hemihydrate, the second exothermic reaction at higher temperature ranges cannot be overlooked in wet-calcined hemihydrates.…”
Section: Methodsmentioning
confidence: 49%
“…The exotherm did not appear in the range observed in the hemihydrate powders (about 2200C), but it did appear at a higher temperature range of about 350 to 4500C. It is reasonable to expect the exothermic reaction to occur in this high-temperature range, since the dehydration conditions produced in the DTA apparatus are considered to be similar to those prevailing in many dry calcination methods (Fleck et al, 1960;Kuntze, 1965;Miyazaki, 1966;Holdridge and Walker, 1967); therefore, a dry-calcined hemihydrate, which is characterized by an exotherm at a high-temperature range (Powell, 1958), was formed during the dehydration of the DTA-TG specimens. In the specimens containing additives, the exothermic reaction was the one most affected by the addition of both H3BO3 and NaCI; the peak was shifted to higher temperatures by about 50°C with H3BO3 and to lower temperatures by about 150°C with NaCl.…”
Section: Methodsmentioning
confidence: 89%
“…The differences observed in the exothermic effects are possibly associated with the dehydration kinetics dependent on surface area, porosity, crystallinity, etc. [11,15,16]. Opposite to these observations, Budnikov and Kosyreva [17] have claimed that the thermogram of the -form does not exhibit an exothermic effect.…”
Section: Thermal Behaviourmentioning
confidence: 99%